The Influence of Jasmine Aromatherapy on the Sleep Quality of Stroke Patients at Bogor Hospital in 2023 - Anastasia Dian Parlina; Agus Purnama; Susaldi Susaldi (UIMA Press, 2024)
Introduction: Stroke results in ongoing cognitive impairments that lead to increased blood pressure, heart attacks, and psychological issues such as depression and sleep quality disorders. The impact of untreated sleep quality disorders can hinder the rehabilitation or recovery process. The sleep quality issues experienced by stroke patients can be addressed through both pharmacological and non-pharmacological therapies, including the use of complementary therapy such as jasmine aromatherapy. Objective: To determine the effect of jasmine aromatherapy on the sleep quality of stroke patients. Methode: The design or type of research used in this study is experimental research. It employs a Non-Equivalent Control Group or Non-Randomized Control Group Pretest-Posttest design. Results: Research was conducted on 36 samples in the intervention group that were given jasmine aromaterapy . The effect size was 2,36 and in the control group the p value was found to be 0,058 with an effect size of 0,491. Conclusion: There is an effect before and after the administration of jasmine aromatherapy.